Comparison of healing of full-thickness skin wounds grafted with multidirectional or unidirectional autologous artificial dermis: differential delivery of healing biomarkers (2018)
Cytokines, chemokines, and growth and remodeling factors orchestrate wound healing when skin damage occurs. During early stages, when the wound is still open, detection and quantification of these compounds might provide biomarkers of skin wound healing, which could aid to complete the scenario provided by clinical follow-up data and histological and histomorphometric analyses. This work assessed and compared the healing of full-thickness skin wounds grafted with artificial dermis made with autologous skin fibroblasts and unidirectional or multidirectional type I collagen scaffolds to test this hypothesis. Biomarkers of healing were detected and quantified in the culture medium of artificial dermis and exudates from the grafted wounds. Clinical follow-up of animals and histological and histomorphometric analysis showed differences in graft integration, wound closure, and histological and histomorphometric parameters. Surface plasmon resonance quantification of 13 healing biomarkers indicated differential secretion of most of the quantified factors in culture medium by the multidirectional and unidirectional artificial dermis. Also, there were significant differences between the concentration of some of the factors analyzed in the exudates of wounds grafted with the evaluated artificial dermis. These findings suggest that differential delivery of healing biomarkers induced by the directionality of the scaffold used to produce the multidirectional and unidirectional dermis was sufficient to create two skin wound microenvironments that determined a different outcome of healing. Overall, data indicate that healing of wounds grafted with multidirectional autologous artificial dermis is better than that of the wounds grafted with the unidirectional one. © 2018, Controlled Release Society.